Applications of single-cell Raman microspectroscopy in bacteria metabolism and physiology - Xu, Jiabao (2020)
Bacteria play important roles in almost all ecosystems, including the natural environment and the human body, and they are extremely abundant and versatile. New generations of sequencing technologies can provide phylogenetic diversity and metagenomic profiling of microbial communities, but metabolic functions of individual microbes and their molecular mechanisms are often elusive, owing to the limited culturability and the complexity of microbial communities.